2020
DOI: 10.1136/bmjdrc-2020-001447
|View full text |Cite|
|
Sign up to set email alerts
|

Incidence and outcomes of hospitalization for community-acquired, ventilator-associated and non-ventilator hospital-acquired pneumonias in patients with type 2 diabetes mellitus in Spain

Abstract: IntroductionTo describe the incidence and compare in-hospital outcomes of community-acquired pneumonia (CAP), ventilator-associated pneumonia (VAP) and non-ventilator hospital-acquired pneumonia (NV-HAP) among patients with or without type 2 diabetes mellitus (T2DM) using propensity score matching.Research design and methodsThis was a retrospective observational epidemiological study using the 2016–2017 Spanish Hospital Discharge Records.ResultsOf 245 221 admissions, CAP was identified in 227 524 (27.67% with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
(67 reference statements)
2
12
0
Order By: Relevance
“…The results of the present study indicate that during admission for CAP, men and women with T2DM received non-invasive mechanical ventilation more frequently than matched non-T2DM men and women. The overuse of non-invasive mechanical ventilation among people with diabetes has been described previously [7,10]. In a study about mechanical ventilation use in 56,158 patients with CAP who received ventilator support, the authors found an increase in the prevalence of comorbidities over time that could partially explain the higher need for ventilatory support [30].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The results of the present study indicate that during admission for CAP, men and women with T2DM received non-invasive mechanical ventilation more frequently than matched non-T2DM men and women. The overuse of non-invasive mechanical ventilation among people with diabetes has been described previously [7,10]. In a study about mechanical ventilation use in 56,158 patients with CAP who received ventilator support, the authors found an increase in the prevalence of comorbidities over time that could partially explain the higher need for ventilatory support [30].…”
Section: Discussionmentioning
confidence: 96%
“…The PSM was conducted using multivariable logistic regression in which the matching variables were age, sex, and comorbid conditions present at admission. These methods have been described in detail elsewhere [7].…”
Section: Study Design Study Population and Data Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Type 2 diabetes mellitus (T2DM) is becoming more prevalent, especially in younger populations, as dietary and lifestyle habits change (1)(2)(3)(4). Since T2DM is often asymptomatic in its early stages, many patients have poor compliance to treatment.…”
Section: Introductionmentioning
confidence: 99%